Editor's Choice – Outcomes After One Stage Versus Two Stage Open Repair of Type II Thoraco-abdominal Aortic Aneurysms. (March 2019) - Gombert, Alexander; Kirner, Linda; Ketting, Shirley; Rückbeil, Marcia V.; Mees, Barend; Barbati, Mohammad E.; Keschenau, Paula R.; Kalder, Johannes; Schurink, Geert W.; Kotelis, Drosos; Jacobs, Michael J.
Abstract : Objective: This study compared the outcomes of open one stage with open two stage repair of type II thoraco-abdominal aortic aneurysms (TAAA). Methods: This retrospective study included 94 patients (68 men) with a mean ± SD age of 54.5 ± 14 years who underwent open type II TAAA repair from March 2006 to January 2016. The mean aneurysm diameter was 65 ± 14.4 mm. The median follow up was 42 months (range 12–96). Seventy-six patients received one stage open repair and 18 patients were treated in two steps: 12 received two open procedures (thoracic and abdominal) and six received hybrid repair (one open and one endovascular procedure). This study focused on the comparison of open one stage and open two stage TAAA repair. The median time between the two steps was 31.5 days (range 1–169). Results: In hospital mortality after open one stage repair versus open two stage type II repair was 22.4% versus 0% (odds ratio 7.352, 95% confidence interval [CI] 0.884–959.1]; p = .19). The one year survival rate after one stage repair versus open two stage repair was 74.7% (95% CI 62.7–83.3) versus 90.9% (95% CI 50.8–98.7 [ p = .225]). The five year survival rate after one stage repair versus open two stage repair was 53.0% (95% CI 37.2–66.5) versus 90.9% (95% CI 50.8–98.7 [ p = .141]). The hazard ratio for survival after one stage repair and after open two stage repair was 4.563 (95% CI 96.9–81.4 [ p = .137]). Paraplegia was observed after open one stage repair versus open two stage in 10.5% vs. 8% ( p = 1). Acute kidney injury requiring permanent dialysis and myocardial infarction were assessed for after open one stage repair and open two stage and were seen in 3.9% vs. 0% ( p = 1) and in 5.3% vs. 0% ( p = 1), respectively. Conclusion: Open two stage repair may be recommended as a treatment option for type II TAAAs if anatomically feasible, as it has a lower mortality and similar complication rates to one stage repair.